AGE AND GROWTH OF ’GHOL’, PSEUDOSCIAENA DIACANTHUS (LACEPEDE) IN BOMBAY AND SAURASHTRA WATERS - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
IN an earlier paper the present author (Rao, 1961) had shown that the scales and otoliths of ’Ghol’, Pseudosciaena diacanthus (Lacepede), a commercially important sciaenid in Bombay and Saurashtra waters, are useful as age indicators of this species. The results of studies on the growth of this fish based on these structures and the length frequency data for the period 1958-62 are presented here. Further, von Bertalanffy growth equation was fitted to the length-at-age data and estimates of the parameters were obtained and compared with similar estimates of other sciaenids from different regions.